Neoantigen-based mRNA vaccine exhibits superior anti-tumor activity compared to synthetic long peptides in an in vivo lung carcinoma model - Cao Minh Nguyen; Trung T. Vu; Minh Nguyen Nguyen; Thao-Suong Tran-Nguyen; Chi Thien Huynh; Quang Thanh Ha; Hoai-Nghia Nguyen; Le Son Tran (Cancer Immunology, Immunotherapy)
Abstract Neoantigen vaccines hold great promise in cancer immunotherapy, but the comparative efficacy of different vaccine platforms, particularly in the context of tumor burden (TB), remains insufficiently studied. In this research, we evaluated the safety and therapeutic efficacy of synthetic long peptide and mRNA-based vaccines, both designed to target identical neoantigens across different Lewis Lung Carcinoma (LLC) tumor burdens. We employed the LLC syngeneic mouse model, a widely used preclinical model for aggressive and immunosuppressive tumors. Our findings demonstrated that the mRNA-based vaccine significantly outperformed the peptide-based vaccine in preventing tumor growth in mice with low TB. These results underscore the potential of mRNA vaccines as a more effective approach for treating aggressive tumors, contributing valuable insights for the future development of neoantigen-based cancer vaccines.